If b is real such that b 4 + b 4 1 = 6 , find value of ( b + b i ) 1 6 for i = − 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Note first that ( b + b i ) 1 6 = ( ( b + b i ) 4 ) 4 .
Now upon expansion of the binomial, we have that
( b + b i ) 4 = b 4 + 4 b 3 × b i + 6 b 2 × ( b i ) 2 + 4 b × ( b i ) 3 + ( b i ) 4 =
b 4 + 4 b 2 i − 6 − b 2 4 i + b 4 1 = 4 i ( b 2 − b 2 1 ) , since b 4 + b 4 1 − 6 = 0 .
Now ( b 2 − b 2 1 ) 2 = b 4 + b 4 1 − 2 = 6 − 2 = 4 , so b 2 − b 2 1 = ± 2 .
Thus ( b + b i ) 1 6 = ( 4 i × ( ± 2 ) ) 4 = ( ± 8 i ) 4 = 8 4 = 4 0 9 6 .
Wow! Did exactly the same!
Log in to reply
Haha That's good! The other way to do this is to calculate
( ( b + b i ) 2 ) 8 = ( b 2 − b 2 1 + 2 i ) 8 =
( ± 2 + 2 i ) 8 = ( ± 2 2 e ± 4 i π ) 8 = 2 1 2 = 4 0 9 6 .
b^4 + 1/b^4 = 6
b² - 1/b² = 2
b² + i²/b² = 2
Now, ( b + i/b ) ^16 = ( ( b + i/b )² )^8 . = ( b² + i²/b² + 2i )^8 . = ( 2 + 2i)^8 Through binomial expression, we get- . ( 2 + 2i )^8 = 2^8 * 2^4 . = 2^16 =4096
( b + b i ) 1 6 Let, z z 2 − 2 ( z 2 − 2 ) 2 ⟹ z 2 We need z 1 6 = ( i ( i b + b i ) ) 1 6 = ( i b + b i ) 1 6 As, ( i ) 1 6 = 1 = ( i b + b i ) = ( i b 2 + b 2 i ) = − ( b 4 + b 4 1 ) + 2 = − 4 ( b 4 + b 4 1 ) = 6 Given = 2 ± 2 i to find z 1 6 = ( z 2 ) 8 = ( 2 ± 2 i ) 8 = ( 2 2 e ± i 4 π ) 8 = ( 2 1 2 e ± i 2 π ) = 2 1 2 = 4 0 9 6
Problem Loading...
Note Loading...
Set Loading...
( b + b i ) 4 ( b + b i ) 1 6 = b 4 + 4 b 2 i − 6 − b 2 4 i + b 4 1 = 4 i ( b 2 − b 2 1 ) = 4 4 i 4 ( b 2 − b 2 1 ) 4 = 4 4 [ ( b 2 − b 2 1 ) 2 ] 2 = 4 4 [ b 4 − 2 + b 4 1 ] 2 = 4 4 ⋅ 4 2 = 4 0 9 6 Note that b 4 + b 4 1 = 6 Raise both sides to the power of 4